Human Body - Williams, Frances, Dr.; Edited by Smith, Miranda (London Dorling Kindersley, 1997)
This information book covers the human body. Using three dimensional models, it shows just how the body works from the inside out. Accompanying text and annotation show the reader structures usually hidden from view and explain how they work
Include Color Illustrations, Glossary and Index.
Introduces the component parts of the human body and explores the ways in which they function.
Keywords: Human anatomy -- Human body -- Human physiology